Borderline phyllodes tumor with cystic squamous metaplasia: a case report - Iqbal Singh; Kalpesh Vaghela; Jignesh Dangi; Bhargavi R. Patel (MGM Journal of Medical Sciences)
Phyllodes tumors (PTs) are uncommon fibroepithelial neoplasms of the breast, comprising only 0.3% to 1% of all primary breast tumors. Metaplastic changes are rare, with cystic squamous metaplasia (CSM) being an exceptionally uncommon finding that can mimic malignancy. Here, we present the case of a 36-year-old female with a rapidly enlarging, painful mass in the right breast, initially suspected to be malignant (Breast imaging reporting and data system category IV). The patient underwent fine-needle aspiration cytology followed by a simple mastectomy. Subsequent histopathological examination confirmed a borderline PT with rare CSM. The tumor exhibited stromal proliferation, moderate atypia, and focal infiltrative borders. Due to its rarity and potential diagnostic challenges, recognizing CSM in PTs is essential for accurate diagnosis and appropriate management.